AVATAR 2.0: next level communication systems for radiotherapy through face-to-face video, biofeedback, translation, and audiovisual immersion - Schulz, Joseph B.; Zalavari, Laszlo; Gutkin, Paulina; Jiang, Alice; Wang, Yi-Peng; Gibson, Clinton; Garza, Aaron; Bush, Karl K.; Wang, Lei; Donaldson, Sarah Susan; Loo, Billy W.; Hiniker, Susan M.; et al. (Frontiers in Oncology, 2024)
PurposeThis paper discusses an advanced version of our audiovisual-assisted therapeutic ambience in radiotherapy (AVATAR) radiolucent display systems designed for pediatric radiotherapy, enabling anesthesia-free treatments, video communication, and biofeedback. The scope of the AVATAR system is expanded here in two major ways: (i) through alternative mounting systems to accommodate a broader range of radiotherapy machines (specifically to fit robotic-arm and toroidal geometry photon radiotherapy and proton radiotherapy systems) and (ii) through additional hardware to provide video-calling, optimized audio for clear communication, and combined video inputs for biofeedback, translation, and other advanced functionalities.Methods and materialsBecause robustness requires strong parts and radio-transparency requires thin, light parts, three-dimensional printing was used to rapidly prototype hollow structures and to iteratively improve robustness. Two system designs were made: one that mounts superior and another that mounts inferior to the patient’s head. Radiation dose measurements and calculations were conducted to assess dose perturbations at surface and depth due to the screen.ResultsFor 6-MV volumetric modulated arc therapy (VMAT) plans, with and without the screen, the mean and maximum dose differences inside the planning target volume were 0.2% and 2.6% of the 200 cGy prescription, respectively. For a single static beam through the screen, the maximum measured excess surface dose was 13.4 ± 0.5%, and the largest measured dose attenuation at 5-cm water-equivalent depth was 2.1 ± 0.2%. These percentages are relative to the dose without the screen at those locations.ConclusionsThe radiolucent screen systems provided here are shown to give minimal dosimetric effects on megavoltage VMAT photon treatments. For static beams, however, surface dose effects should be considered when these beams pass through the thickest components of the screen. Design files are also provided.